2020
DOI: 10.1029/2019gl086817
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of Cloud‐Radiation Interactions in Subseasonal Tropical Disturbances

Abstract: Cloud locking, a method that prescribes cloud properties for radiative tendency calculations, is traditionally used to explore climate feedbacks, but here is applied novelly to investigate cloud-radiation interaction (CRI) impacts on subseasonal tropical variability. The approach minimizes mean state differences between control (CRI active) and experimental simulations (CRI disabled) of the Community Earth System Model. Disabling CRI weakens amplitudes of the Madden-Julian oscillation (MJO) by 10-35% and equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 71 publications
5
15
0
Order By: Relevance
“…Another approach is to lock the CREs by providing cloud fields to the radiative transfer calculation that are independent of the flow field. By using cloud fields from a separate simulation with a given model, this approach has been shown to maintain the mean climate very well 8,12,47,48 . The approach maintains the spatial, seasonal, and diurnal structure of CRE, but instantaneously removes the correlation between the atmospheric state and the clouds as seen by the radiative transfer.…”
Section: Cloud-locking Experimentsmentioning
confidence: 99%
See 4 more Smart Citations
“…Another approach is to lock the CREs by providing cloud fields to the radiative transfer calculation that are independent of the flow field. By using cloud fields from a separate simulation with a given model, this approach has been shown to maintain the mean climate very well 8,12,47,48 . The approach maintains the spatial, seasonal, and diurnal structure of CRE, but instantaneously removes the correlation between the atmospheric state and the clouds as seen by the radiative transfer.…”
Section: Cloud-locking Experimentsmentioning
confidence: 99%
“…The cloud-locking approach has been applied to CESM2 in both coupled and prescribed-SST configurations. The simulations have been described in detail in previous studies 12,48 ; we denote them using c (coupled) and f (fixed SST) modifying either "control" or "lock". Relevant to the present application, it has been shown that cloud-radiative feedbacks alter tropical variability 12 .…”
Section: Cloud-locking Experimentsmentioning
confidence: 99%
See 3 more Smart Citations